2019
DOI: 10.1016/j.bbrep.2019.100687
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic inhibition of cell-to-cell HIV-1 infection by combinations of single chain variable fragments and fusion inhibitors

Abstract: Cell-to-cell spread of HIV permits ongoing viral replication in the presence of antiretroviral therapy and is suggested to be a major contributor to sexual transmission by mucosal routes. Fusion inhibitors that prevent viral entry have been developed, but their clinical applications have been limited by weak antiviral activity, short half-life, and the low genetic barrier to development of resistance. We examined the inhibitory activities of a series of single-chain variable fragments (scFvs) targeting the V3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…By the use of the NFκB-inhibitor Minocyclin, cell fusion has been markedly reduced [129]. Additional cell fusion inhibitors have been used to inhibit HIV cell-free and cell-cell infections [130][131][132][133]. In summary, cell fusion is an important process in tissue regeneration, but it also might lead to the development of different diseases, if this process is dysregulated.…”
Section: Cell Fusion and Stem Cellsmentioning
confidence: 99%
“…By the use of the NFκB-inhibitor Minocyclin, cell fusion has been markedly reduced [129]. Additional cell fusion inhibitors have been used to inhibit HIV cell-free and cell-cell infections [130][131][132][133]. In summary, cell fusion is an important process in tissue regeneration, but it also might lead to the development of different diseases, if this process is dysregulated.…”
Section: Cell Fusion and Stem Cellsmentioning
confidence: 99%
“…This may be especially true for epitopes in close proximity such as the V2 and V3, or V3 and CD4bs. A recent study demonstrated that scFv targeting the V3 and CD4bs could display synergy when combined with fusion inhibitors ( 37 ).…”
Section: Introductionmentioning
confidence: 99%